2020
DOI: 10.34172/jlms.2020.65
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of the Metal Bracket to Zirconium Ceramic Restoration Treated by the Nd: YAG Laser and Other Methods: An In Vitro Microscopic Study

Abstract: Introduction: Providing reliable bonding of the bracket base and the zirconia surface is required to apply orthodontic force. The purpose of this scientific experiment was to evaluate the efficacy of three different methods of surface preparation for Zirconia, including surface roughening, sandblasting and the Nd: YAG laser, in the shear bond strength (SBS) of the orthodontic brackets. Methods: Fifty-four discs of zirconia were divided into three groups of 18: A) Hydrofluoric acid etching, B) sandblasting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A different study also found sufficiently high SBS values using the combination of CoJet and RXP, although the SBS values were lower and very close to the lower limit of the recommended values 28 . In general, the literature is very controversial as some studies found that air-abrasion and silane application results in sufficient SBS 19 , 29 and others reported contrary findings 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A different study also found sufficiently high SBS values using the combination of CoJet and RXP, although the SBS values were lower and very close to the lower limit of the recommended values 28 . In general, the literature is very controversial as some studies found that air-abrasion and silane application results in sufficient SBS 19 , 29 and others reported contrary findings 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In orthodontic bracket bonding to zirconia, it is essential to create a reliable bond strength to withstand orthodontic and masticatory forces. 14 Nonetheless, orthodontic bracket bonding on ceramic restorations may increase the surface roughness (due to surface treatment or residual resin removal), change the esthetic appearance of restoration, decrease its longevity, enhance plaque retention, leading to periodontal problems and restoration discoloration. 15 Since zirconia is devoid of glass phase, hydrofluoric acid cannot be used to enhance its bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for adult orthodontic treatment and the growing popularity of esthetic dentistry, clinicians face challenges when bonding orthodontic brackets onto various types of dental restorations compared to enamel [ 1 , 2 , 3 ]. Zirconium is widely recognized as one of the most used materials for all-ceramic crowns, offering advantages such as esthetic appearance, biocompatibility, and resistance.…”
Section: Introductionmentioning
confidence: 99%